"By what authority?" The contested politics of urban toponymic inscription in Zimbabwe. Issue 1 (2nd January 2023) - Mamvura, Zvinashe
ABSTRACT: This article explores the contest over the naming of urban landscapes in Zimbabwe. The analysis unfolds from the realization that urban landscapes are significant in naturalizing political systems and ideologies. Political actors strive to control and configure urban landscapes in a way that popularizes their political ideologies. This study advances the argument that urban local government actors may contest the hegemonic place-naming system that ruling elites prescribe. State actors also block any efforts by subordinate groups to disrupt the harmony between official toponymy and the political ideology that the ruling regimes popularize. However, subordinate groups can be heterogeneous leading to a multi-layered nature of resistance. There can be relations of dominance and subordination among the constituent elements of subordinate groups. Preliminary findings indicate that there is legislative ambivalence within and between the Urban Councils Act (Chapter 29:15) of 1996 and the Constitution of Zimbabwe, Amendment No. 20 of 2013, that allows for conflicting interpretations of arenas and boundaries of authority over urban toponymic inscription between urban local government actors and the central state. This causes perennial conflicts between central government and urban local government actors.